Characterization and effects of DDG on the intake and digestibility of finishing bulls in feedlots - Fonseca, Natália Vilas Boas [UNESP]; Cardoso, Abmael Da Silva [UNESP]; Hoffmann, Alvair; Leite, Rhaony Gonçalves [UNESP]; Ferrari, Adriana Cristina [UNESP]; Fernandes, Marcia Helena Machado Da Rocha [UNESP]; Reis, Ricardo Andrade [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2020)
The aim of this study was to characterize four corn and sorghum co-products (DDG) in terms of their protein and carbohydrate fractions; we also evaluated the effects of substituting the protein source of the conventional supplement by DDG on consumption and nutrient digestibility in confined finishing cattle. Thirty-six male Nellore cattle with a mean age of 24 months were used. The treatments were: FA: concentrate with corn as an energy source and cottonseed meal as a protein source; DDG50: concentrate with a 50% substitution of the FA protein source by DDG; DDG100: concentrate with 100% substitution of the FA protein source by DDG. The experimental design was completely randomized with three treatments and three replicates (pens) containing four animals per pen. We found that the use of DDG in the finishing phase did not interfere with the animals’ food intake or the digestibility of the nutrients (p > 0.05). Nutrients were used by the animals; therefore, DDGs may be viable substitutes of cottonseed meal. We conclude that the bromatological composition of this co-product is influenced a lot during processing; therefore, the nutritional values of this co-product present in the composition tables may not be true.
Keywords: cattle; co-products; confinement; corn ethanol; fractionation of nitrogen compounds; animal nutrition